Anti-Cancer Phytometabolites Targeting Cancer Stem Cells - F.V. Torquato, Heron; I. Goettert, Marcia; Z. Justo, Giselle; J. Paredes-Gamero, Edgar (Current Genomics, 2017)
Medicinal plants are a plentiful source of bioactive molecules with much structural diversity. In cancer treatment, molecules obtained from plants represent an attractive alternative to other treatments because several plant-derived compounds have exhibited lower toxicity and higher selectivity against cancer cells. In this review, we focus on the possible application of bioactive molecules obtained from plants against more primitive cell populations in cancers, cancer stem cells. Cancer stem cells are present in several kinds of tumors and are responsible for recurrences and metastases. Common anticancer drugs exhibit lower effectiveness against cancer stem cells because of their biological features. However, recently discovered natural phytometabolites exert cytotoxic effects on this rare population of cells in cancers. Therefore, this review presents the latest research on promising compounds from plants that can act as antitumor drugs and that mainly affect stem cell populations in cancers.
Keywords: Cancer stem cells